DAMPAK REVITALISASI PASAR TRADISIONAL TERHADAP EKONOMI PEDAGANG KIOS DI PASAR CIK PUAN KOTA PEKANBARU - Lista Yarnis; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Cik Puan traditional market in Pekanbaru City. The purpose of this research is to characterize booth traders in traditional market Cik Puan Pekanbaru City. The focus of this research is the impact of the market revitalization process on the merchant economy at Pasar Cik Puan Market of Pekanbaru. The technique of determining the sample in simple random sampling and set the number of samples as many as 9 people. The writer uses quantitative descriptive method and Instrument data is observation, questionnaire and documentation. The research found there are some revitalization of Cik Puan Pekanbaru market, which are as follows: The builder's socialization, as evidenced by the respondents' responses (61.7%) revealed that the government never regularly review the Cik Puan market development. Deliberation, respondents justify (78.3%) the absence of sustainable development on market Cik Puan Pekanbaru. The emergence of Interpersonal Conflict, the expected response from the government traders is very poor (76.7%). Some Impacts of the Cik Puan Traditional Market Revitalization Process are as follows: The Household Traders' Economic Deficit, starting from the Cik Puan Market development plan until now traders are not reaping any changes in their trading activities except the drastic reduction in income. Many Merchants Business Roll Mats, 93.3% of respondents feel and get a bad impact of market revitalization on sale and purchase transactions. Customers who used to be many, now half did not appear since the process of market development took place. Keywords: Social Change, Development, Traditional Traders